Guidelines for publishing in education JCR journals in German, English and Spanish - Llorent-Bedmar, Vicente (2018)
We have analysed and compared the requirements and evaluation criteria of education reviews with the highest Impact Factor indexed in JCR (2015) in German, English and Spanish. We provide key aspects for researchers interested in publishing articles in these journals, in order to give useful information to promote quality education publications. After indicating its position in JCR (Journal Citations Report) and its IF (Impact Factor), we compared the review criteria used in these journals for the evaluation of manuscripts using the methodology of Comparative Education. Results show most of the evaluation criteria are focused on the evaluation of new contributions; the importance of the subject; the quality of the abstract; the rigor and methodological adequacy; the theoretical grounds; quotations and references; and its originality.